Anaphoric relations in English and French : a discourse perspective - Cornish, Francis (Routledge library editions : the English language., 2015)
First published in 1986, this book focuses on Anaphoric relations in the English and French languages, a phenomenon that involves a complex interaction between grammar and discourse. Studies of anaphora taking a largely 'textual' approach to the subject have tended to underestimate the effect upon its formation of referential and discourse factors, while studies framed within a psycholinguistic and computational perspective have been inclined to minimise the importance of the purely linguistic features connected with anaphora. This volume places the study of anaphora upon a firmer foundation b.